Hollow nano composite material as well as preparation method and application thereof
By developing the hollow nanocomposite material Au NBPs@CuS, we have solved the problem of low light conversion efficiency of existing single nanomaterials, achieved efficient photothermal conversion and inhibited amyloid aggregation, and improved its potential in biomedical applications. clinical value.
Patent Information
- Application Number
- CN202411476962.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The low photoconversion efficiency of existing single nanomaterials leads to poor clinical therapeutic effects in biomedical applications, limiting their application in inhibiting Alzheimer's disease-related amyloid aggregation.
A hollow nanocomposite material, Au NBPs@CuS, was developed. By using gold nanobipyramids as the core center and compounding the nanostructure of the hollow p-type semiconductor CuS on the outer layer, its photothermal and photodynamic properties were improved.
The improvement of light thermal conversion efficiency has reached 43.88%. Under the light, it can generate active oxygen 1o2 and · OH, significantly inhibit the aggregation of amyloid -like proteins, and can effectively inhibit the production of fibers under non -light conditions.
Smart Images

Figure CN119345357A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material technology, and in particular relates to a hollow nanocomposite material and a preparation method and application thereof. Background Art
[0002] Alzheimer's disease (AD) is an aging neurodegenerative disease characterized by memory impairment, executive dysfunction, behavioral changes, etc., which seriously threatens human health. Although the pathogenic mechanism of AD is still unclear, the mainstream theory believes that the aggregation of amyloid protein monomers (Aβm) into oligomers and the formation of fiber aggregates are the key steps in the onset of AD, among which soluble oligomers (Aβo) and insoluble fibrils (Aβf) are considered to be the key to neuronal toxicity.
[0003] In recent years, nanomaterials have played a wide range of roles in inhibiting the aggregation of Aβ proteins due to their photothermal and photodynamic properties. Among them, copper sulfide (CuS) nanomaterials, as p-type semiconductors with narrow band gaps, trigger the dd band transition of Cu(II) ions under near-infrared laser irradiation, resulting in photothermal properties. Gold nanobipyramids (Au NBPs), as an emerging excellent plasmonic light-absorbing nanomaterial, have the ability to improve light utilization efficiency and hot electron generation. Compared with other materials, Au NBPs have sharp double ends, which show stronger light absorption effect and improve the "light enrichment" effect. However, single nanomaterials often fail to produce satisfactory clinical treatment results due to their relatively low light conversion efficiency, which greatly limits their application in biomedicine. Therefore, the development of composite nanomaterials with strong photothermal properties will provide new ideas for the removal of Aβ. Summary of the invention
[0004] The purpose of the embodiments of the present application is to provide a hollow nanocomposite material, aiming to solve the problems of low light conversion efficiency, poor clinical treatment results, and limited application in biomedicine of existing single nanomaterials.
[0005] The embodiment of the present application is implemented as follows: a hollow nanocomposite material, wherein the hollow nanocomposite material is a nanostructure with a gold nanobipyramid as the core center and a composite hollow p-type semiconductor as the outer layer;
[0006] The structural formula of the hollow nanocomposite material is Au NBPs@CuS, wherein CuS is an outer semiconductor and AuNBPs is an inner core.
[0007] Preferably, the particle size of the hollow nanocomposite material is 125-135 nm.
[0008] The present application also provides a method for preparing the above-mentioned hollow nanocomposite material, comprising:
[0009] Prepare gold nanobipyramids; the particle size of the gold nanobipyramids is 95 to 105 nm;
[0010] The gold nanobipyramids are dropped into a sodium polystyrene sulfonate solution and stirred evenly to obtain a mixture of Au NBPs@PSS;
[0011] The mixture NBPs@PSS is dropped into the polyvinyl pyrrolidone solution and stirred evenly to obtain a mixture AuNBPs@PSS@PVP;
[0012] 5-10 mL of the mixture Au NBPs@PSS@PVP is added to an aqueous solution containing 1-2 mL of copper nitrate and 9-18 mL of polyvinyl pyrrolidone, followed by rapid addition of 12.8-25.6 μL of hydrazine monohydrate solution for reaction, and then addition of 0.415-0.83 mL of sodium sulfide solution for uniform stirring to obtain a hollow nanocomposite material.
[0013] The hollow nanocomposite material Au NBPs@CuS provided in the embodiment of the present application is a nanostructure with a gold nanobipyramid Au NBPs as the core and a hollow p-type semiconductor CuS as the outer layer. By combining Au NBPs with CuS, not only is the photothermal performance greatly improved, the photothermal conversion efficiency reaches 43.88%, but also active oxygen can be generated under light. 1 O2 and ·OH, excellent photothermal effect and photodynamic performance provide theoretical support for the application in inhibiting amyloid aggregation. The hollow nanocomposite Au NBPs@CuS can inhibit the formation of fibers under non-light conditions. ThT fluorescence experiments have confirmed that Au NBPs@CuS can effectively inhibit Aβ at very low concentrations. 42 The transition from random curl structure to β-folded structure; Atomic force microscopy experiments confirmed that Au NBPs@CuS can effectively reduce the fiber content. In addition, under the stimulation of exogenous NIR, the hollow Au NBPs@CuS nanocomposite has strong photothermal efficiency, which can convert light energy into heat energy and quickly heat up to 60°C in a short time, breaking up the already formed fibers.
[0014] The hollow nanocomposite material preparation method provided in the embodiment of the present application prepares the hollow Au NBPs@CuS composite material by adopting the principle and technology of surface modification and Kirkendall effect, realizing the first combination of p-type semiconductor CuS and gold nanobipyramids. The tip effect of Au NBPs is better than that of Au NPs synthesized in the past, and its ultraviolet absorption reaches the maximum at 808nm, and the phototherapy performance is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 A schematic diagram of the synthesis of the hollow nanocomposite Au NBPs@CuS provided in the examples of the present application;
[0016] Figure 2 TEM (A, B) and EDS (CF) images of the hollow nanocomposite material Au NBPs@CuS provided in Example 1 of the present application;
[0017] Figure 3 The cooling time constant diagram (A) of the hollow nanocomposite material Au NBPs@CuS provided in Example 1 of the present application and the ESR diagram (B) of the active oxygen species of Au NBPs@CuS under light irradiation;
[0018] Figure 4 The different concentrations of Au NBPs@CuS provided in the examples of this application inhibit Aβ 42 The kinetic curve of aggregation;
[0019] Figure 5 The hollow nanocomposite Au NBPs@CuS provided in the present embodiment depolymerizes Aβ 42 AFM images of the fibers. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0021] The embodiment of the present application provides a hollow nanocomposite material, wherein the hollow nanocomposite material is a nanostructure with a gold nanobipyramid as the core center and a hollow p-type semiconductor as the outer layer;
[0022] The structural formula of the hollow nanocomposite material is Au NBPs@CuS, wherein CuS is an outer semiconductor and AuNBPs is an inner core.
[0023] The particle size of the hollow nanocomposite material is 125-135nm. Under 808nm infrared laser irradiation, its concentration is between 10μg / mL and 60μg / mL, which has good photothermodynamic properties. In addition, when its concentration is between 50μg / mL and 100μg / mL, it can absorb 808nm near-infrared light and heat up quickly in a short time. In addition, the hollow nanocomposite material can generate active oxygen under the induction of near-infrared light. 1 O2 and OH.
[0024] like Figure 1The synthetic route shown in the embodiment of the present application provides a method for preparing the above-mentioned hollow nanocomposite material, comprising:
[0025] Preparation of gold nanobipyramids;
[0026] The gold nanobipyramids are dropped into a sodium polystyrene sulfonate solution and stirred evenly to obtain a mixture of Au NBPs@PSS;
[0027] The mixture NBPs@PSS is dropped into the polyvinyl pyrrolidone solution and stirred evenly to obtain a mixture AuNBPs@PSS@PVP;
[0028] 5-10 mL of the mixture Au NBPs@PSS@PVP is added to an aqueous solution containing 1-2 mL of copper nitrate and 9-18 mL of polyvinyl pyrrolidone, followed by rapid addition of 12.8-25.6 μL of hydrazine monohydrate solution for reaction, and then addition of 0.415-0.83 mL of sodium sulfide solution for uniform stirring to obtain a hollow nanocomposite material.
[0029] The particle size of the gold nanobipyramid is 95-105 nm, and its ultraviolet absorption is around 780-790 nm.
[0030] In one embodiment of the present application, the method for preparing the gold nanobipyramids (Au NBPs) comprises:
[0031] 2.8 mL of deionized water, 4 mL of 0.1 M hexadecyltrimethylammonium chloride (CTAC), 200 μL of 10 mM HAuCl4, and 400 μL of 0.1 M citric acid were vigorously stirred at room temperature, and then 100 μL of 0.05 M glacial NaBH4 was added, and the mixture was stirred at 80 °C for 1.5 hours to obtain a seed solution;
[0032] 50-80 μL of the seed solution was added to a mixed solution containing 32 μL of 0.1 M ascorbic acid (AA), 4 mL of 0.1 M hexadecyltrimethylammonium bromide, 200 μL of 0.01 M HAuCl4, 40 μL of 0.01 M AgNO3 and 80 μL of 2 M HCl, and kept at 30°C for 3 hours to obtain gold nanobipyramids.
[0033] Optionally, the synthesis method of gold nanobipyramids can be specifically as follows: first, CTAC (0.1M, 4mL), HAuCl4 (10mM, 200μL) and citric acid (0.1M, 400μL) are added to 2.8mL of stirring deionized water in sequence; then, freshly prepared ice-cold NaBH4 (0.05M, 100μL) is added to the solution; then, the solution is placed in an oil bath at 80°C and 380rpm for 90 minutes, and the final color turns red; the obtained seed solution is stored at 4°C for subsequent use. CTAB (0.1M, 4mL), HAuCl4 (0.01M, 200μL), AgNO3 (0.01M, 40μL) and HCl (2M, 80μL) are added to a 10mL glass bottle in sequence, and finally AA (0.1M, 32μL) is added. After the solution becomes colorless, 50 to 80μL of seed solution is added. The mixture was kept at 30°C for 3 hours, washed by centrifugation, dispersed in water, and stored at 4°C.
[0034] The ultraviolet absorption wavelength of the gold seed solution is 520 nm. When the added volume of the seed solution is 80 μL, the particle size of the obtained Au NBPs is 100 nm.
[0035] It is worth noting that the present invention first synthesizes Au NBPs with a longitudinal plasma peak near 780nm, and then modifies its surface from CTAB stabilization to PSS and PVP coating, thereby changing its positive charge to negative charge, thereby enabling Cu 2+ The Au NBPs@CuS nanocomposite synthesized in this application has strong photothermal efficiency and uses a power of 1.2-1.5W / cm 2 The nanocomposite material is irradiated with near-infrared light having a wavelength of 808 nm, so that the temperature is raised to 60-70° C. in 5±1 min, and the photothermal conversion efficiency is high.
[0036] In one embodiment of the present application, the step of dropping the gold nanobipyramids into a sodium polystyrene sulfonate solution and stirring evenly to obtain a mixture of Au NBPs@PSS comprises:
[0037] The gold nanobipyramids were dropped into a sodium polystyrene sulfonate solution containing 6 mM NaCl and stirred overnight to obtain a mixture AuNBPs@PSS.
[0038] In one embodiment of the present application, the concentration of the sodium polystyrene sulfonate solution is 2 g / L, and the volume ratio of the sodium polystyrene sulfonate solution to the added gold nanobipyramids is 1:1.
[0039] In one embodiment of the present application, the step of dripping the mixture Au NBPs@PSS into a polyvinyl pyrrolidone solution and stirring evenly to obtain a mixture Au NBPs@PSS@PVP comprises:
[0040] The mixture Au NBPs@PSS solution was dropped into an equal volume of 20 g / L polyvinyl pyrrolidone solution and stirred for 3 hours to obtain a mixture Au NBPs@PSS@PVP.
[0041] Optionally, the preparation method of the hollow nanocomposite material can be specifically as follows: the gold nanobipyramid solution obtained above is dripped into 5mL of PSS solution (2g / L, 6mM NaCl). Stir overnight to obtain Au NBPs@PSS solution; then the Au NBPs@PSS solution is dripped into PVP solution (20g / L, 5mL), and after stirring for three hours, Au NBPs@PSS@PVP solution is obtained; copper nitrate (1-2mL, 0.1M) solution is added to 9-18mL of aqueous solution containing 0.2-0.4g PVP; after stirring for 15 minutes, 5-10mL of Au NBPs@PSS@PVP mixture is added, followed by rapid addition of 12.8-25.6μL, 17.5wt% monohydrate hydrazine solution, after reacting for 10 minutes, 0.415mL, 0.2M sodium sulfide solution is added, and continuous stirring is performed for 2 hours to obtain a hollow AuNBPs@CuS composite material.
[0042] In one embodiment of the present application, the concentration of the mixture Au NBPs@PSS@PVP is 4.5 mM. The mixture is centrifuged at 1200 rpm for 6 minutes and washed three times with anhydrous ethanol and deionized water.
[0043] In one embodiment of the present application, the rotation speed during stirring is 650-800 rpm, preferably 700 rpm.
[0044] The embodiments of the present application also provide a use of the above-mentioned hollow nanocomposite material in inhibiting the aggregation of β-amyloid protein fibers and / or breaking up β-amyloid protein fiber aggregates.
[0045] Among them, when the hollow Au NBPs@CuS nanocomposite was used to inhibit the aggregation of amyloid protein, different materials were combined with Aβ 42 The specific co-incubation steps can be: CuS, Au NBPs (2.72 μg / mL), Au NBPs+CuS (2.72 μg / mL+10.72 μg / mL) or Au NBPs@CuS (containing 2.72 μg / mL Au NBPs and 10.72 μg / mL CuS) are respectively incubated with Aβ 42(25 μM) were mixed in a stock solution of PBS buffer (pH = 7.4). When the hollow nanocomposite Au NBPs@CuS was used to inhibit the depolymerization of amyloid, the power used was 1.2-1.5 W / cm 2 The hollow nanocomposite material and the prefabricated fiber were irradiated with near-infrared light of wavelength 808 nm, and the temperature was raised to 60°C in 5±1 min to break up the formed fiber. The results show that the hollow nanocomposite material Au NBPs@CuS formed by combining Au NBPs with CuS has a strong inhibitory effect on Aβ 42 The inhibition or depolymerization effect of the fibers is superior to that of Au NBPs, CuS single materials and simple physical composites of Au NBPs+CuS.
[0046] Examples of certain embodiments of the present application are given below, which are not intended to limit the scope of the present application.
[0047] In addition, it should be noted that the numerical values given in the following examples are as accurate as possible, but those skilled in the art understand that due to unavoidable measurement errors and experimental operation problems, each number should be understood as an approximate number rather than an absolutely accurate value.
[0048] Example 1
[0049] (1) Preparation of Au NBPs: 2.8 mL of deionized water, 4 mL of 0.1 M CTAC, 200 μL of 10 mM HAuCl4, and 400 μL of 0.1 M citric acid were added to a 10 mL glass bottle in sequence. After vigorous stirring at room temperature for 2 min, freshly prepared ice-cold 100 μL of 0.05 M NaBH4 was quickly added to the solution at once; the mixture turned from light yellow to brown. The solution was then placed in an 80 °C oil bath for 1.5 h under stirring at 380 rpm, causing the color to gradually change from brown to red. The prepared seed solution was stored at 4 °C for subsequent use. To synthesize Au NBPs, 200 μL of 0.01 M HAuCl4, 40 μL of 0.01 M AgNO3, and 80 μL of 2 M HCl were added dropwise to a solution containing CTAB (0.1 M, 4 mL) in sequence. 32 μL of 0.1 M ascorbic acid was added under continuous stirring, and the color of the solution was observed to fade to colorless within 30 seconds. Then, 80 μL of the prepared gold seed solution was added to the growth solution system. Finally, the mixture was allowed to stand at 30 °C for 3 hours. After centrifugation at 7000 rpm for 10 minutes and washing once with deionized water, the Au NBPs were redispersed in 4.504 mL of deionized water and stored at 4 °C for later use.
[0050] (2) Synthesis of hollow nanocomposite Au NBPs@CuS: A 6mM NaCl solution of PSS (2g / L, 5mL) was added to a glass bottle, and then 5mL of Au NBPs was added dropwise. It was stirred overnight, centrifuged at 7000rpm for 10 minutes, and then redispersed in 5mL of deionized water. The Au NBPs@PSS solution was then dropped into 5mL of 20g / L PVP solution. Stirring was continued for 3 hours. The resulting Au NBPs@PSS@PVP solution was centrifuged and dispersed in deionized water. 1mL of 0.1M Cu(NO3)2·3H2O solution was added to 9mL of an aqueous solution containing 0.2g of polyvinylpyrrolidone (PVP, MW=58000) and stirred for 15 minutes. Then, 5 mL of the prepared Au NBPs@PSS@PVP (4.5 mM) mixture solution was added, followed by the rapid addition of 13.8 μL of 17.5 wt% hydrazine monohydrate solution. The solution turned yellow-brown, and after 10 minutes of reaction, 0.415 mL of 0.2 M sodium sulfide nonahydrate solution was added to the mixture, and the hollow nanocomposite Au NBPs@CuS was obtained after stirring for two hours. Finally, the product was collected by centrifugation and washed with ethanol and deionized water for further characterization.
[0051] Example 2
[0052] (1) Preparation of Au NBPs: 2.8 mL of deionized water, 4 mL of 0.1 M CTAC, 200 μL of 10 mM HAuCl4, and 400 μL of 0.1 M citric acid were added to a 10 mL glass bottle in sequence. After vigorous stirring at room temperature for 2 minutes, 100 μL of freshly prepared ice-cold 0.05 M NaBH4 was quickly added to the solution at one time. The mixture turned from light yellow to brown. The solution was then placed in an 80 °C oil bath for reaction for 1.5 hours with stirring at 380 rpm, causing the color to gradually change from brown to red. The prepared seed solution was stored at 4 °C for subsequent use. To synthesize Au NBPs, 200 μL of 0.01 M HAuCl4, 40 μL of 0.01 M AgNO3, and 80 μL of 2 M HCl were added dropwise to a solution containing CTAB (0.1 M, 4 mL). 32 μL of 0.1 M ascorbic acid was added under continuous stirring, and the color of the solution was observed to fade to colorless within 30 seconds. Then, 80 μL of the prepared gold seed solution was added to the growth solution system. Finally, the mixture was allowed to stand at 30 °C for 3 hours. After centrifugation at 7000 rpm for 10 minutes and washing once with deionized water, the Au NBPs were redispersed in 4.504 mL of deionized water and stored at 4 °C for later use.
[0053] (2) Synthesis of hollow nanocomposite Au NBPs@CuS: A 6mM NaCl solution of PSS (2g / L, 5mL) was added to a glass bottle, and then 5mL of Au NBPs was added dropwise. It was stirred overnight, centrifuged at 7000rpm for 10 minutes, and then redispersed in 5mL of deionized water. The Au NBPs@PSS solution was then dropped into 5mL of 20g / L PVP solution. Stirring was continued for 3 hours. The resulting Au NBPs@PSS@PVP solution was centrifuged and dispersed in deionized water. 2mL of 0.1M Cu(NO3)2·3H2O solution was added to 18mL of an aqueous solution containing 0.4g of polyvinylpyrrolidone (PVP, MW=58000) and stirred for 15 minutes. Then, 10 mL of the prepared Au NBPs@PSS@PVP (4.5 mM) mixture solution was added, followed by the rapid addition of 27.6 μL of 17.5 wt% hydrazine monohydrate solution. The solution turned yellow-brown, and after 10 minutes of reaction, 0.83 mL of 0.2 M sodium sulfide nonahydrate solution was added to the mixture, and the hollow nanocomposite Au NBPs@CuS was obtained after stirring for two hours. Finally, the product was collected by centrifugation and washed with ethanol and deionized water for further characterization.
[0054] The characterization results of Examples 1-2 are consistent. The characterization results of Example 1 are described below. The morphology of the hollow nanocomposite Au NBPs@CuS prepared in Example 1 was characterized by field emission transmission electron microscopy. The results are as follows: Figure 2 Specifically, the morphology and size distribution of the hollow nanocomposite Au NBPs@CuS were characterized by field emission transmission electron microscopy (JEM-200F, JEOL, Japan) using ultrathin carbon films. Figure 2 The results show that when 5 mL of the above-prepared Au NBPs@PSS@PVP was added as the core for synthesis, the particle size was uniform and had an obvious hollow core-shell structure. The Cu and S elements were distributed in the core-shell, and the Au element was distributed in the core. The dispersion was uniform and the average particle size was 125 nm, confirming the successful synthesis of the hollow nanocomposite material AuNBPs@CuS under this condition.
[0055] Furthermore, the photothermal and photodynamic properties of the hollow nanocomposite Au NBPs@CuS prepared in Example 1 were characterized as follows:
[0056] (1) Photothermal performance test
[0057] The wavelength is 808nm and the power is 1.5W / cm 2The Au NBPs@CuS solution was irradiated with a laser, and the temperature was recorded every 30 seconds for a total of 5 minutes. After that, the heating was stopped and the solution was allowed to cool naturally to room temperature. The cooling temperature curve over time was recorded. The calculation formula for the photothermal conversion efficiency (η) is as follows:
[0058]
[0059] Among them, h, S, T max , T sur and Q s represents the heat transfer coefficient, the container surface area, the equilibrium temperature, the ambient temperature, and the heat associated with the light absorption rate of the tube and water. I and A represent the laser power and absorbance of the solution at 808 nm, respectively. D Indicates the weight of water, c D The specific heat capacity of water (4.2 J g -1 ℃ -1 ), τ represents the time constant of Au NBPs@CuS during cooling. t(s) is the irradiation time, and τ can be calculated according to the linear regression curve.
[0060] like Figure 3 As shown in Figure 2, Au NBPs and CuS composites have greatly improved photothermal performance, and their photothermal conversion efficiency has reached 43.88%, R 2 is 0.99.
[0061] (2) Detection of reactive oxygen species
[0062] 2,2,6,6-Tetramethylpiperidine and 5-tert-butyloxycarbonyl-5-methyl-1-pyrroline N-oxide were used as 1 O2 and ·OH scavengers were used to identify active oxygen species. At 808 nm, the power was 1.5 W / cm 2 The cells were irradiated with laser for 10 min to determine the production of ROS under light.
[0063] Furthermore, the effect of the hollow nanocomplex prepared in Example 1 on the aggregation morphology of Aβ42 and the disaggregation of Aβ42 fibers were studied as follows:
[0064] (1) Effect of hollow nanocomposite Au NBPs@CuS on Aβ 42 Effect of aggregation morphology
[0065] CuS (10.72 μg / mL), Au NBPs (2.72 μg / mL), Au NBPs+CuS (2.72 μg / mL+10.72 μg / mL) or Au NBPs@CuS (containing 2.72 μg / mL Au NBPs and 10.72 μg / mL CuS) were respectively added to Aβ 42 (25 μM) was mixed in a stock solution of PBS buffer (pH = 7.4). At the same time, in order to monitor the appearance and growth of the fibers, Aβ 42 A 15 μL aliquot of the sample was added to 235 μL ThT (24 μM). The fluorescence intensity of the solution was then measured using a fluorescence spectrophotometer (excitation wavelength 440 nm, emission wavelength 485 nm), and the results can indicate Aβ 42 The amount of fibrils, the results Figure 4 shown.
[0066] The synthesis method of CuS is as follows: copper nitrate (1 mL, 0.1 M) solution is added to 9 mL of an aqueous solution containing 0.2 g of PVP, stirred for 15 minutes, and then 5 μL of a 35 wt% hydrazine monohydrate solution is quickly added. After reacting for 10 minutes, 0.3 mL of a 0.2 M sodium sulfide solution is added, and stirred continuously for 2 hours to obtain a hollow CuS material.
[0067] (2) Effect of hollow nanocomposite Au NBPs@CuS on Aβ 42 Effect of pre-fiber depolymerization
[0068] After 24 h of culture, Aβ 42 After the fiber was incubated with different materials and exposed to light for 10 minutes, 10 μL of the sample was dropped on the mica sheet, and then slowly rinsed with deionized water after standing for 30 minutes to remove the salt ions in the solution. The rinsed mica sheet was blown dry with nitrogen and scanned in tapping mode.
[0069] like Figure 4 As shown, Au NBPs@CuS and Aβ 42 The co-incubation kinetic curve shows that the fiber content is extremely low. The results show that Au NBPs@CuS has a strong affinity for Aβ 42 The strongest inhibitory effect was observed in the incubation of fibroblasts. Figure 5 The AFM images shown in the figure show that Aβ 42 After 24 h, dense fibrous aggregates were formed. 42 After irradiation, the fibers disappeared and the depolymerization effect was the strongest compared with other materials. The depolymerization effect of Au NBPs@CuS was better than that of CuS, Au NBPs and the simple physical mixture of CuS+Au NBPs.
[0070] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
[0071] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A hollow nanocomposite material, characterized in that: The hollow nanocomposite material is a nanostructure with a gold nanobipyramid as the core and a composite hollow p-type semiconductor as the outer layer; The structural formula of the hollow nanocomposite material is Au NBPs@CuS, wherein CuS is an outer semiconductor and Au NBPs is an inner core.
2. The hollow nanocomposite material according to claim 1, characterized in that: The particle size of the hollow nanocomposite material is 125-135 nm; the particle size of the gold nanobipyramid is 95-105 nm.
3. A method for preparing the hollow nanocomposite material according to claim 1 or 2, characterized in that: include: Prepare gold nanobipyramids; the particle size of the gold nanobipyramids is 95 to 105 nm; Dropping the gold nanobipyramids into a sodium polystyrene sulfonate solution and stirring evenly to obtain a mixture of Au NBPs@PSS; The mixture NBPs@PSS is dropped into the polyvinyl pyrrolidone solution and stirred evenly to obtain a mixture Au NBPs@PSS@PVP; 5-10 mL of the mixture Au NBPs@PSS@PVP is added to an aqueous solution containing 1-2 mL of copper nitrate and 9-18 mL of polyvinyl pyrrolidone, followed by rapid addition of 12.8-25.6 μL of hydrazine monohydrate solution for reaction, and then addition of 0.415-0.83 mL of sodium sulfide solution for uniform stirring to obtain a hollow nanocomposite material.
4. The method for preparing the hollow nanocomposite material according to claim 3, characterized in that: The method for preparing the gold nanobipyramids comprises: 2.8 mL of deionized water, 4 mL of 0.1 M hexadecyltrimethylammonium chloride, 200 μL of 10 mM HAuCl4, and 400 μL of 0.1 M citric acid were vigorously stirred at room temperature, and 100 μL of 0.05 M glacial NaBH4 was added, and stirred at 80°C for 1.5 hours to obtain a seed solution; 50-80 μL of the seed solution was added to a mixed solution containing 32 μL of 0.1 M ascorbic acid, 4 mL of 0.1 M hexadecyltrimethylammonium bromide, 200 μL of 0.01 M HAuCl4, 40 μL of 0.01 M AgNO3 and 80 μL of 2 M HCl, and kept at 30° C. for 3 hours to obtain gold nanobipyramids.
5. The method for preparing the hollow nanocomposite material according to claim 3, characterized in that: The step of dropping the gold nanobipyramids into a sodium polystyrene sulfonate solution and stirring evenly to obtain a mixture of Au NBPs@PSS comprises: The gold nanobipyramids were dropped into a sodium polystyrene sulfonate solution containing 6 mM NaCl and stirred overnight to obtain a mixture AuNBPs@PSS.
6. The method for preparing the hollow nanocomposite material according to claim 3 or 5, characterized in that: The concentration of the sodium polystyrene sulfonate solution was 2 g / L, and the volume ratio of the added gold nanobipyramids was 1:
1.
7. The method for preparing the hollow nanocomposite material according to claim 3, characterized in that: The step of dripping the mixture Au NBPs@PSS into a polyvinyl pyrrolidone solution and stirring the mixture to obtain a mixture Au NBPs@PSS@PVP comprises: The mixture Au NBPs@PSS solution was dropped into an equal volume of 20 g / L polyvinyl pyrrolidone solution and stirred for 3 hours to obtain a mixture Au NBPs@PSS@PVP.
8. The method for preparing the hollow nanocomposite material according to claim 3, characterized in that: The concentration of the mixture AuNBPs@PSS@PVP is 4.5 mM.
9. The method for preparing the hollow nanocomposite material according to claim 3, characterized in that: The concentration of copper nitrate is 0.1M; the concentration of sodium sulfide is 0.2M.
10. Use of the hollow nanocomposite material according to claim 1 or 2 in inhibiting the aggregation of β-amyloid protein fibers and / or breaking up β-amyloid protein fiber aggregates.
Citation Information
Patent Citations
Different-morphology gold nanoparticle bipyramid-gold and silver nanoparticle composite material and preparation method thereof
CN108746595A
PH-responsive composite nano material based on hollow copper sulfide and ruthenium complex, preparation method of nano material and application of nano material in medicines for treating cancers
CN110384799A
Preparation method of gold nano bipyramid / cadmium sulfide core-shell structure
CN111589455A
Gold nanomaterial with hollow core-shell structure under near-infrared II region excitation condition as well as preparation method and application of gold nanomaterial
CN117583593A
Hollow copper sulphide nano-particles loaded with tetravalent platinum drug and preparation and application of hollow copper sulphide nano-particles
CN118512603A